WITHDRAWN: Do multiple credit ratings reduce money left on the table? Evidence from U.S. IPOs - Goergen, Marc; Gounopoulos, Dimitrios; Koutroumpis, Panagiotis (Journal of Corporate Finance, 2020)
This article has been withdrawn at the request of the authors and will be logged in with a new article number. The Publisher apologizes for any inconvenience this may cause. The full Elsevier Policy on Article Withdrawal can be found at https://www.elsevier.com/about/our-business/policies/article-withdrawal